The oral trial centrality in the Accusatory System: a strategic view of criminal case - Raphael Jorge De Castilho Barilli (Revista Brasileira de Direito Processual Penal)
This paper aims to discuss the orality as the methodological center of the accusatory system, indicating an administration of justice format based on the case. To this end, we seek to point out that the written process form, which for a long time has been placed as the ideal process format, is insufficient due to the notable influence of diverse elements, which cannot be formally appropriated, influencing the outcome of the case. In this context of oral litigation, it is necessary to ask: Is there a strategy for presenting the elements in the oral debate? How is the notion of strategy in criminal litigation seen by the law community? At what moments in the process should this strategic action be implemented? These and other issues will be addressed in this exhibition, which has as methodology the theoretical investigation of literature regarding this new framework, concluding that the notion of strategy is a natural consequence of the new procedural paradigm. In addition, this modern thinking process is seen as a trend in the context of criminal procedural reform in Latin America in the last decades, which seeks to overcome the inquisitive nuances of the process, affirming an accusatory system of a truly democratic adversarial tendency.